A novel three-dimensional evaluation protocol to assess the consistency of critical screw angles between preoperative planning and 3d-printed patient-specific acetabular revision prostheses - Luo, Dinghao; Wu, Junxiang; Ran, Zhaoyang; Wu, Wen; Wang, Lei; Xie, Kai; Hao, Yongqiang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundScrew fixation is pivotal for prosthetic stability. For 3D-printed customized acetabular revision prostheses designed for complex, large-scale bone defects, precise adherence to preoperative screw trajectory planning is critical. However, there remains a lack of standardized three-dimensional (3D) evaluation protocols to quantify intraoperative screw angular alignment fidelity relative to preoperative digital plans, hindering universal validation criteria.MethodsA total of 11 patients were stratified into two groups based on postoperative Harris Hip Scores and severe complication rates: the better outcome group and the regular outcome group. A 3D pelvic coordinate system was established using anatomical landmarks. Two biomechanically critical screws per prosthesis were selected to quantify 3D angular deviations between postoperative and preoperative plans. The efficacy of this method was compared with simulated anteroposterior radiograph-based 2D measurements. Inter- and intra-observer consistency (kappa statistics) were evaluated to assess reproducibility.ResultsHigh inter-observer (κ = 0.88) and intra-observer (κ = 0.87, 0.75) agreement confirmed method reliability. While individual critical screw deviations showed no significant intergroup differences, the cumulative angular deviation of critical screws was significantly lower in the better outcome group (p = 0.0147). In contrast, 2D radiographic analysis failed to distinguish intergroup differences in cumulative deviations (p = 0.1489), demonstrating reduced clinical relevance.ConclusionThis 3D assessment protocol robustly correlates with clinical outcomes, providing a validated tool for evaluating preoperative-to-postoperative fidelity in customized acetabular revision prostheses. To our knowledge, this is the first CT-based 3D coordinate system study quantifying critical screw alignment accuracy in patient-specific prostheses, with clinical validation.